Peningkatan Keterampilan Praktis Hukum Melalui Pelatihan Penyusunan Gugatan Perdata Bagi Mahasiswa Fakultas Hukum Universitas Halu Oleo - Satriani Satriani; Pipit Somefotorono Majid; Besse Sari Angraeni; Mutia Nur Fadhilah Ruslan; Andi Khaedhir Kamri; Risman Setiawan (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
The ability to draft civil lawsuits constitutes one of the essential practical competencies that must be possessed by law students, particularly those who are preparing to enter legal professions such as advocates, judges, prosecutors, and legal consultants. However, legal education in higher education institutions is often dominated by theoretical approaches, resulting in limited opportunities for students to develop practical litigation skills, especially in drafting civil procedural documents. This community service activity aimed to improve the practical legal skills of students of the Faculty of Law, Universitas Halu Oleo, through training on the preparation of civil lawsuit documents. The activity was conducted in collaboration with the Moot Court Community of the Faculty of Law, Universitas Halu Oleo, using a participatory and practice-based learning approach. The methods employed included lectures, interactive discussions, case analysis, document review, and simulation exercises involving the preparation of civil lawsuits based on case scenarios designed to encourage legal reasoning and analytical skills. The results of the activity demonstrated a significant improvement in participants' understanding of the formal and substantive requirements of civil lawsuits, the structure and systematic drafting of pleadings, and the relationship between legal facts, legal arguments, and legal remedies sought in court. Participants also showed enhanced abilities in identifying legal issues, determining the appropriate parties and legal grounds for litigation, and preparing coherent and executable claims. Furthermore, the activity contributed to strengthening students' confidence in engaging in legal practice and promoted the development of practice-oriented legal education within the Faculty of Law, Universitas Halu Oleo.